2011
DOI: 10.1017/s001447971100038x
|View full text |Cite
|
Sign up to set email alerts
|

MAIZE (ZEA MAYS) LEAF ANGLE AND EMERGENCE AS AFFECTED BY SEED ORIENTATION AT PLANTING

Abstract: Maize (Zea mays ) seed orientation at planting can influence emerging leaf angle. If leaf angle were consistent among plants without leaf overlap, large numbers of these bilaterally symmetrical plants could be arranged to optimize light interception and possibly increase grain yields or maintain grain yield with a lower population. The objectives were to evaluate the effect of seed orientation in soil on the angle of maize leaves relative to the planted row and on emergence rate. Seeds were planted 2.5 cm deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…This assumption was verified as feasible in developing FAPAR-P model. However, the leaf angle distribution of maize is also found to be variable with seed orientation [58] and phenological stages [59]. The use of more precise description of leaf angle distribution could thus be considered in other work.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption was verified as feasible in developing FAPAR-P model. However, the leaf angle distribution of maize is also found to be variable with seed orientation [58] and phenological stages [59]. The use of more precise description of leaf angle distribution could thus be considered in other work.…”
Section: Discussionmentioning
confidence: 99%
“…Strategic positioning of seeds in the planting furrow may allow the leaves to be oriented in the horizontal plane perpendicularly to the sowing row, which would reduce leaf overlap (shading) and thus increase PAR interception and grain yield (Fortin & Pierce, 1996;Toler, Murdock, Stapleton, & Wallace, 1999;Torres, Vossenkemper, Raun, & Taylor, 2011;Taiz, Moller, & Murphy, 2017;Sangoi, Ender, Guidolin, Almeida, & Heberle, 2001). Fortin and Pierce (1996) suggested that the random orientation of maize ear leaves is a result of random positioning of seeds in the furrow.…”
Section: Introductionmentioning
confidence: 99%
“…As stated by Toler et al (1999), this phenomenon occurs when the seed is placed vertically with the tip pointing down in the soil and the embryo facing the middle of the inter-row, which results in higher grain yields than when the seed is sown randomly. In addition to this position, Torres et al (2011) sowed flat seeds horizontally with the dorsal face down and found this position to be beneficial for leaf orientation, as it prevented shading.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations